Modernization and accountability in the social economy sector - Ferreira, Augusta da Conceicao Santos, 1966- (Business Science Reference, 2019)
"This book explores the future avenues of development in the management of social economy sectors (SES), including accounting, control in SES management, and measures of performance in SES management"--